Suprascapular nerve entrapment in a patient with spinal cord injury - FACIONE, J.; BEIS, JM; KPADONOU GODONOU, TOUSSAINT; LAGAUCHE, D; TOUILLET, A.; BRAUN, M.; CHAPELAIN Le, L.; PAYSANT, J. (My University, 2011)
.
Keywords: paraplegia; spinal cord injuries; Suprascapular nerve entrapment; shoulder pain; overuse